Perbedaan Segitiga Cinta pada Dewasa Awal Berdasarkan Jenis Kelamin dan Jarak - Prisilia, Roma Setya; Kristinawati, Wahyuni (Widya Cakra: Journal of Psychology and Humanities; Vol 1 No 3 (2021): Volume 1 Nomor 3 Tahun 2021 - Widya CakraDO - 10.24843/widyacakra.2021.v1.i3.p77991, 2022)
One of the specific developmental tasks for emerging adults is developing intimate relationships with the opposite sex (Santrock, 2011). This study aims to examine the differences between the three components of the love triangle theory (intimacy, passion, and commitment) for men and women who are in a Long Distance Relationship (LDR) and Proximal Relationship (PR). This study has hypotheses that the level of intimacy component in women is higher than men, the level of passion component in men is higher than women, the level of decision/commitment component in men is higher than women, the level of intimacy component in Proximal Relationship couples is higher. higher than Long Distance Relationship, passion component level in Long Distance Relationship is higher than Proximal Relationship, decision/commitment component level in Long Distance Relationship is higher than Proximal Relationship. This study involved 136 respondents and used a comparative quantitative approach. The results found in this study were that there were no differences in the level of the three components in emerging adults who underwent dating relationships based on sex except for the intimacy component of sig. value (1-tailed) of 0.0285 (p < 0.05) where men are higher than women with a significant difference and there is no difference in the level of the three components in emerging adulthood who dating relationships based on distance except for the passion component with a sig. value (1-tailed) of 0.0005 (p < 0.05) where the long distance relationship couples is higher than the proximal relationship couples with a significant difference.